International business in Turkey: an experiencial learning method / Maznah Wan Omar and NazirulMubinbin Mohd Noor - Wan Omar, Maznah; Mohd Noor, NazirulMubinbin (Faculty of Business and Management, 2019)
The Turkish economy has followed a roller-coaster ride in the past several decades. Following an anemic performance with severe imbalances in the 1990s and a debilitating financial crisis in 2001. An Experiential learning method used through a survey conducted in two cities in Turkey, which is Istanbul and Bursa for a period of two weeks. Systematic review method used to enhance the collected materials. Turkey enjoyed five years of rapid economic growth, with GDP per capita increasing at almost 6% per annum – its highest ever rate since the 1960s – accompanied by structural changes, productivity growth and a broadening base of economic activity, both geographically and socially. From about 2007 onwards, however, economic growth slowed significantly, and productivity growth stagnated for all practical purpose.